Ligand Rotation Distinguishes First- and Second-Generation Ruthenium Metathesis Catalysts - Adlhart, Christian; Chen, Peter (Angewandte Chemie International Edition, 2002)
QM/MM provides a new twist: In olefin metathesis with first‐generation Ru catalyst 1, the rotation of the phosphane ligand with threefold symmetry is the rate‐determining step. Second‐generation catalyst 2 is more active: the rotation step is not required as the carbene ligand has twofold symmetry. Combined QM/MM calculations confirm the results of earlier experimental investigations.